Pengaruh Keputusan Investasi, Profitabilitas, Likuiditas, serta Struktur Modal terhadap Nilai Perusahaan: (Studi Empiris pada Perusahaan Sub Sektor Makanan Olahan & Minuman yang terdaftar di BEI Periode 2019-2023) - Diva Mahira Azzahra; Ansisa Amalia Mulya (Jurnal Mutiara Ilmu Akuntansi, 2025)
This study aims to determine the effect of investment decisions, profitability, liquidity, and capital structure on firm value, and to analyze investment decisions, profitability, liquidity, and capital structure on firm value. The population in this study are processed food and beverage sub-sector companies listed on the Indonesia Stock Exchange in the financial statements for the 2019-2023 period. The sampling technique in this study used purposive sampling method and obtained a sample of 31 companies. The analysis technique used is multiple linear regression analysis using SPSS software version 22.0. The results of this study indicate that investment decisions have a significant effect on Firm Value, Profitability has a significant effect on Firm Value, Liquidity has no significant effect on Firm Value, and Capital Structure has a significant effect on Firm Value.